Adverse effects of extracorporeal carbon dioxide removal (ECCO2R) for acute respiratory failure: a systematic review protocol. Issue 1 (December 2016) - Liu, Zulian; Duarte, Rui; Bayliss, Sue; Bramley, George; Cummins, Carole
Abstract Background The extracorporeal membrane carbon dioxide removal (ECCO2 R) system is primarily designed for the purpose of removing CO2 from the body for patients with potentially reversible severe acute hypercapnic respiratory failure or being considered for lung transplantation. Systematic reviews have focused on the effectiveness of ECCO2 R. To the author's best knowledge, this is the first systematic review to focus on the adverse effects of this procedure. Methods We will conduct a systematic review of procedure-related adverse effects of ECCO2 R systems. A high sensitivity search strategy will be employed in Cochrane Library, MEDLINE, EMBASE, Web of Science and product regulatory databases and ongoing trial registers to identify citations. Reference lists of relevant studies and grey literature will also be searched. Screening of the results will be performed by two reviewers independently using pre-defined inclusion and exclusion criteria. Clinical trials and observational studies will be included. Data will be extracted using a purposefully developed extraction form. Appropriateness for statistical pooling of the results will be determined and carried out if heterogeneity is low to moderate. The GRADE framework will be employed to grade the overall quality of the evidence. Discussion In the UK, the current access to the use of ECCO2 R is possible only with special arrangements for clinical governance, consent and for audit or research. Current evidence on ECCO2 R suggests that there are a number of well-recognised complications which vary greatly across studies. This systematic review will consolidate the existing knowledge on adverse effects resulting from the use of ECCO2 R. Systematic review registration PROSPEROCRD42015023503 .